(untitled) (Papeles, 2024)
The coverage of social contingencies has had its greatest development around a budget: registered work in a dependency relationship. This entails a contributory coverage scheme, based mainly on financing through contributions from workers and employers. In this work, we will synthesize the various coverage systems for social contingencies - old age, disability, death, illness, work accident, family responsibilities, maternity, unemployment - for registered workers, and which constitute the central structure of the public policy of protection. However, we do not fail to point out that, in a context with high rates of labor informality, a large part of the population is left out of that Social Security contributory umbrella. For this group of people, non-contributory or assistance schemes subsidiarily establish protection against social contingencies. This leads to the need to design public policies in line with the current reality, which contemplate various situations and modalities: informal work, independent work, teleworking/work 4.0, care work, migrant work/digital nomads.